Analisis Hubungan Kemitraan Pemerintah Daerah, Swasta, dan Masyarakat dalam Pelaksanaan Corporate Social Responbility (CSR) PT Vale Indonesia Bidang Pendidikan dan Kesehatan Kabupaten Luwu Timur - Arya Utama; Andi Murfhi (Departemen Ilmu Pemerintahan Fisip Unhas, 2017)
This study aims to determine the relationship between government, private, and community partnership in the implementation of Corporate Social Responsibility (CSR) programs of PT. Vale Indonesia Education and Health field in East Luwu Regency as well as influential factors in it. The research method used is qualitative research by parsing data descriptively. Data collection technique is done by observation, interview, literature study, and documentation by using qualitative descriptive analysis technique. The results of this study indicate that partnerships built in the implementation of Corporate Social Responsibility (CSR) between the Government, Private and society especially in the field of education and health is not maximized. This can be seen from the communication between the two actors in the cooperation run harmoniously and lasted in two direction. However, such cooperation is not written into the Memorandum of Understanding (MoU), so partnership is false. The pattern of partnership that is built is certainly influenced by several factors that support or inhibit. Supporting factors include policies related to Corporate Social Responsibility (CSR), Government involvement, private, and community as actors in the management of CSR programs. Inhibiting factors include Communication and Related Coordination of CSR Program in the Education and Health Sector.